Dead is just a rumor / 4. - Perez, Marlene (Perez, Marlene. Dead is., 2010)
Psychic teen Daisy Giordano has her hands full trying to find out who is behind the blackmail letters being sent to paranormal residents of Nightshade, while also worrying about her werewolf boyfriend going away to college and the possibly lethal cooking lessons she is taking with a sinister chef.